Contributory Factors and Clinical Manifestations of Post Natal Depressive Illness in Women - Komal, Naima; Rehan Khan, Samina; Zohra, Sadaf; Aslam, Qurat-u-lain; Mohsin, Rabia; Abdul Waris, Hafsa; Tariq, Amera (Pakistan Armed Forces Medical Journal, 2026)
Objective: To determine frequency, severity and related socio-demographic and clinical variables of postpartum depression (PPD) using validated screening tools in postpartum women.Study Design: Cross-sectional Study.Place and Duration of Study: Pak Emirates Military Hospital Rawalpindi, Pakistan from Jul 2024 to Jul 2025Methodology: This cross-sectional analytical study enrolled 2,000 postpartum women presenting for routine follow-up visits between 6 to 10 weeks to 1 year after delivery at a tertiary care hospital in Rawalpindi. Depressive symptoms were assessed using the Edinburgh Postnatal Depression Scale (EPDS) as the primary screening tool, with the Patient Health Questionnaire-9 (PHQ-9) and Generalized Anxiety Disorder-7 (GAD-7) administered concurrently to capture the broader burden of comorbid depression and anxiety.Results: Using a validated screening threshold of EPDS ≥13, one in three women (33.8%) screened positive for clinically significant postpartum depressive symptoms. Concurrent administration of the PHQ-9 and GAD-7 corroborated these findings, with 29.5% of participants meeting the threshold for moderate-to-severe depression and 26.7% falling within the clinically significant range for anxiety. Multivariate logistic regression identified inadequate social support, a prior history of psychiatric illness, and obstetric complications as the strongest independent predictors of PPD.Conclusion: This research found that almost 1/3 of postpartum women had met clinically significant depressive symptoms, which is greater than the prevalence found in high-income nations.